2020
DOI: 10.1177/0950422220954319
|View full text |Cite
|
Sign up to set email alerts
|

The strategic transformation of accounting into a learned profession

Abstract: The skills gap in the accounting profession is not a new issue. More than 30 years of research and studies all point to an ever-increasing disparity between what accountants do and what the mainstream accounting curriculum teaches. Technology and businesses are changing and evolving rapidly, as are the expectations for accountants. Advances in the areas of automation and machine learning, artificial intelligence, data analytics and blockchain are examples of current technology disruptions in the accounting ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Comparing our SLR to the analysis of curricula composition, there is a clear gap, which points to the need to review and restructure the accounting study plans-an idea supported by international regulatory bodies such as IAESB and the International Federation of Accountants (IFAC) [71,72]. Active teaching methodologies should be put into practice, as the example of the pause method applied by Chen et al [73] in two HEIs in China that revealed significant differences (t-tests compared two neutral responses) for five items for both university groups: communication skills (oral communication skills, written communication skills, interpersonal communication skills); beneficial to the learning process; and a more enjoyable learning experience.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing our SLR to the analysis of curricula composition, there is a clear gap, which points to the need to review and restructure the accounting study plans-an idea supported by international regulatory bodies such as IAESB and the International Federation of Accountants (IFAC) [71,72]. Active teaching methodologies should be put into practice, as the example of the pause method applied by Chen et al [73] in two HEIs in China that revealed significant differences (t-tests compared two neutral responses) for five items for both university groups: communication skills (oral communication skills, written communication skills, interpersonal communication skills); beneficial to the learning process; and a more enjoyable learning experience.…”
Section: Discussionmentioning
confidence: 99%
“…Universities are likely to be lowly ranked if serious attention is not given to the improvement in quality (Materu, 2007;Pereira et al, 2020). There is, thus, an increasing demand for the assessment and evaluation of undergraduate accounting courses (Aldredge et al, 2021). Administrators of accounting programmes have access to little information/ feedback (because of a lack of research) to aid in raising the standard of accounting education and graduates' performance (Adaboh, 2014;Aldredge et al, 2021;Awayiga et al, 2010;Boateng and Sarpong, 2002;Osei and Dontwi, 2014;Tsevi, 2015).…”
Section: Quality Of the Accounting Programmesmentioning
confidence: 99%
“…These developments also have some implications for accounting and finance professionals; BCT may change job definitions and responsibilities (Church et al, 2020). Consequently, the content of accounting education should also conform to those new technologies and developments (Aldredge et al, 2020;Henage, 2020;Qasim and Kharbat, 2020).…”
Section: Integration Of Blockchain With Accounting Information Systemsmentioning
confidence: 99%